Nudging epidemic policy compliance: experimental insights into message framing - Xu, Biao; Yidilisi, Patiman; Xi, Hailing; Gu, Shuyan (Frontiers in Public Health, 2025)
ObjectiveAchieving widespread voluntary public compliance is critical for effective epidemic management. This study investigates how different message-framing strategies influence individuals’ willingness to comply with public health measures during a simulated epidemic scenario.MethodsUsing a randomized 2 × 2 experimental design, we tested the relative effectiveness of four framing conditions—gain-private, loss-private, gain-social, and loss-social—on compliance intentions. Participants (N = 391) were randomly assigned to one of these conditions or a no-framing control group. Compliance willingness was assessed through self-reported intentions to adhere to recommended preventive behaviors.ResultsFramed messages significantly increased compliance intentions compared to the control condition. Among framing strategies, the loss-social frame (emphasizing negative societal consequences of noncompliance) demonstrated the strongest effect, followed by gain-private, gain-social, and loss-private frames. Pairwise comparisons revealed important interactions: gain-framing was more effective within private motivational contexts, whereas loss-framing was particularly compelling within social contexts. Critically, loss-social messages were significantly superior to loss-private ones, while gain-social and gain-private messages performed similarly.ConclusionStrategic message framing effectively enhances public compliance during epidemic crises, with loss-social framing emerging as the most potent approach. These findings offer critical insights for policymakers and health communicators, recommending targeted use of loss-social messaging to optimize public adherence to epidemic prevention guidelines.